Widening of the electroactivity potential range by composite formation – capacitive properties of TiO2/BiVO4/PEDOT:PSS electrodes in contact with an aqueous electrolyte - Trzciński, Konrad; Szkoda, Mariusz; Nowak, Andrzej P.; Łapiński, Marcin; Lisowska-Oleksiak, Anna (Beilstein Journal of Nanotechnology, 2019)
Composites based on the titania nanotubes were tested in aqueous electrolyte as a potential electrode material for energy storage devices. The nanotubular morphology of TiO2 was obtained by Ti anodization. TiO2 nanotubes were covered by a thin layer of bismuth vanadate using pulsed laser deposition. The formation of the TiO2/BiVO4 junction leads to enhancement of pseudocapacitance in the cathodic potential range. The third component, the conjugated polymer PEDOT:PSS, was electrodeposited from an electrolyte containing the monomer EDOT and NaPSS as a source of counter ions. Each stage of modification and deposition affected the overall capacitance and allowed for an expansion of the potential range of electroactivity. Multiple charge/discharge cycles were performed to characterize the electrochemical stability of the inorganic–organic hybrid electrode. Capacitance values higher than 10 mF·cm−2 were maintained even after 10000 galvanostatic cycles (ic = ia = 0.5 mA·cm−2).
Keywords: bismuth vanadate (BiVO4); electrochemical activity; PEDOT:PSS; supercapacitors; titania nanotubes